The Reporting of Corporate Social Responsibility (CRS): Information Sources and Documentation - Dopazo, María Pilar (Revista General de Información y Documentación, 2012)
The compromising towards the CSR includes not only the good global government, discipline, sense of duty, transparency and accountability, but also ethical compromising, participation and dialogue with stakeholders. This article aims to contribute to the establishment of a more structurally of Reporting Corporate -information and documentation of CSRoriented framework for analyzing the Social Responsibility (SR) of the enterprise. To this end, the article resumes the main actions and instruments of reporting integrating the Corporate Social Responsibility (CSR) and the principles of the Sustainability Developed by the systems management of organizations private sector/public sector.